Esposos y amantes consanguíneos entre los tobas (qom) del Gran Chaco - Florencia Tola (Journal de la Société des Américanistes)
Based on material collected among the Toba (Qom) of the Gran Chaco, this article reveals central aspects of the Toba (Qom) kinship system that point to the existence of endogamous marriage patterns. Until now, ethnographic works on this region have characterized the Toba people as a group with a propensity to openness, supposedly expressed in the field of kinship by a generalized exogamy in marriage patterns. After describing the state of the field of regional studies about kinship, this article analyzes an extensive marriage network and the clandestine relationships within it to shed light on the ways in which the choice of spouses and lovers takes place over eight generations.